Nanoscale modulation of electronic states across unit cell steps on the surface of an epitaxial colossal magnetoresistance manganite film - Rana, Abhimanyu; Bogle, Kashinath A.; Game, Onkar S.; Patil, Shankar; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2010)
The nature of electronic states near the edge of unit cell steps on the surface of epitaxial La(0.7)Sr(0.3)MnO(3) (LSMO) thin films grown by real-time reflection high energy electron diffraction monitored pulsed laser deposition is examined by scanning tunneling microscopy and scanning tunneling spectroscopy techniques. It is observed that the electronic states are strongly modulated near the step edge with considerably high gap at the edge and low gap on the terrace. This modulation weakens at low temperature. The temperature evolution of the density of states and the nature of gap in deep metallic state of LSMO are also discussed. (C) 2010 American Institute of Physics. [doi:10.1063/1.3455886]
Keywords: colossal magnetoresistance; electronic density of states; lanthanum compounds; magnetic epitaxial layers; Nanostructured materials; pulsed laser deposition; reflection high energy electron diffraction; scanning tunnelling microscopy; scanning tunnelling spectroscopy; strontium compounds

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy

Lamellar melting, not crystal motion, results in softening of polyoxymethylene on heating - Kumaraswamy, Guruswamy; Surve, Nikita S.; Mathew, Renny; Rana, Abhimanyu; Jha, Saroj K.; Bulakh, Neelima N.; Nisal, Anuya; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Ratnagiri, Ram (Macromolecules, 2012)
We probe temperature-dependent changes in the semicrystalline microstructure of polyoxymethylene using a combination of modulated DSC, SAXS, and solid-state NMR to characterize macroscopic behavior, lamellar-level structure, and molecular environments, respectively, and correlate these with the change in mechanical properties probed using DMA and AFM. Two model samples are investigated: a melt crystallized sample prepared by injection molding and a sample obtained by crystallization from dilute solution. Our investigations reveal that, for both samples, there is an increase in crystalline motions and in the amorphous content on heating. DMA and AFM measurements reveal that the modulus of the molded sample decreases on heating to about 100 degrees C; however, there is a significant difference in behavior of the solution crystals, where we observe no significant decrease in stiffness (from AFM measurements). Thus, in contrast to previous reports, we demonstrate that the decrease in modulus on heating polyoxymethylene does not correlate with chain motions in the crystalline regions. We use SAXS to probe the semicrystalline morphology for the samples on heating and show that, for the molded sample, there is a distribution of lamellar thickness at room temperature and that the thin lamellae in this distribution melt on heating. In contrast to the behavior of the melt crystallized samples, the solution crystals exhibit no change in the lamellar stacking on heating to 150 degrees C. We also demonstrate that, on heating, the amorphous regions in the solution crystals always appear to have restricted mobility while there are mobile and low mobility amorphous regions in the molded samples. Our results suggest that, contrary to conventional belief, the decrease in modulus on heating polyoxymethylene arises not from motions in the crystalline lamellae but primarily from melting of thin lamellae.

Quantum dot bio-conjugate: as a western blot probe for highly sensitive detection of cellular proteins - Kale, Sonia; Kale, Anup; Gholap, Haribhau; Rana, Abhimanyu; Desai, Rama; Banpurkar, Arun G.; Ogale, Satishchandra; Shastry, Padma (Journal of Nanoparticle Research, 2012)
In the present study, we report a quantum dot (QD)-tailored western blot analysis for a sensitive, rapid and flexible detection of the nuclear and cytoplasmic proteins. Highly luminescent CdTe and (CdTe) ZnS QDs are synthesized by aqueous method. High resolution transmission electron microscopy, Raman spectroscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray diffraction are used to characterize the properties of the quantum dots. The QDs are functionalized with antibodies of prostate apoptosis response-4 (Par-4), poly(ADP-ribose) polymerases and beta actin to specifically bind with the proteins localized in the nucleus and cytoplasm of the cells, respectively. The QD-conjugated antibodies are used to overcome the limitations of conventional western blot technique. The sensitivity and rapidity of protein detection in QD-based approach is very high, with detection limits up to 10 pg of protein. In addition, these labels provide the capability of enhanced identification and localization of marker proteins in intact cells by confocal laser scanning microscopy.
Keywords: Detection; Imaging; nanomedicine; quantum dot; Rapid; sensors; Western blot

Scaling behavior of resistive switching in epitaxial bismuth ferrite heterostructures - Rana, Abhimanyu; Lu, Haidong; Bogle, Kashinath A.; Zhang, Qi; Vasudevan, Rama; Thakare, Vishal; Gruverman, Alexei; Ogale, Satishchandra; Valanoor, Nagarajan (Advanced Functional Materials, 2014)
Resistive switching (RS) of (001) epitaxial multiferroic BiFeO3/La0.67Sr0.33MnO3/SrTiO3 heterostructures is investigated for varying lengths scales in both the thickness and lateral directions. Macroscale current-voltage analyses in conjunction with local conduction atomic force microscopy (CAFM) reveal that whilst both the local and global resistive states are strongly driven by polarization direction, the type of conduction mechanism is different for each distinct thickness regime. Electrode-area dependent studies confirm the RS is dominated by an interface mechanism and not by filamentary formation. Furthermore, CAFM maps allow deconvolution of the roles played by domains and domain walls during the RS process. It is shown that the net polarization direction, and not domain walls, controls the conduction process. An interface mechanism based on barrier height and width alteration due to polarization reversal is proposed, and the role of electronic reconstruction at the interface is further investigated.